2020
DOI: 10.3390/buildings11010004
|View full text |Cite
|
Sign up to set email alerts
|

A Competency Model for the Selection and Performance Improvement of Project Managers in Collaborative Construction Projects: Behavioral Studies in Norway and Finland

Abstract: Collaborative work practices are getting more common in construction projects. Consequently, new project delivery models have emerged and new practices have also entered the world of traditional delivery models. The resultant collaborative construction projects provide a different working environment compared to the traditional construction delivery models. This different environment seems to require project managers with certain types of competencies, but there is currently very limited research-based knowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 67 publications
1
22
0
1
Order By: Relevance
“…One way to facilitate inter-organizational communication, learning, commitment, and trust in projects involves the development and implementation of collaborative approaches such as partnering [10][11][12][13]. There is no widely accepted definition of partnering [14], but it can be understood as a formal collaborative model often initiated by the client to avoid conflicts and disputes between the client and contractor, and it includes, for example, workshops, open books, and a facilitator.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One way to facilitate inter-organizational communication, learning, commitment, and trust in projects involves the development and implementation of collaborative approaches such as partnering [10][11][12][13]. There is no widely accepted definition of partnering [14], but it can be understood as a formal collaborative model often initiated by the client to avoid conflicts and disputes between the client and contractor, and it includes, for example, workshops, open books, and a facilitator.…”
Section: Introductionmentioning
confidence: 99%
“…There is no widely accepted definition of partnering [14], but it can be understood as a formal collaborative model often initiated by the client to avoid conflicts and disputes between the client and contractor, and it includes, for example, workshops, open books, and a facilitator. Partnering has been viewed as an effective tool for improved project performance and has, therefore, been implemented in many countries including, for example, the UK [15], Sweden [12], Norway, and Finland [10]. However, earlier empirical studies [16] have found that clients identify three types of barriers to cooperation: cultural (conservative industry culture, adversarial attitudes, short-termism, focus on projects instead of processes, and a lack of supplier involvement), organizational (new competence requirements and traditional construction process and procurement procedures), and industrial (laws and regulations, as well as rules and standard contracts).…”
Section: Introductionmentioning
confidence: 99%
“…Ingle et al [12] investigated the customer relation, safety, schedule, cost, quality, productivity, finance, communication and collaboration, the environment and stakeholder satisfaction in this regard. According to Moradi et al [63], the ability of project managers is of utmost importance for collaborative construction projects. Scheduling is one of the driving factors in the success of the construction project because it guides about when and where to do the work [64,65].…”
Section: Literature Reviewmentioning
confidence: 99%
“…It can be said that this form of construction project delivery implies being collaborative in traditional contracts. In the literature, construction projects with collaborative delivery models (e.g., integrated project delivery, alliance, partnering) and/or traditional ones (e.g., design-bid-build), comprising collaborative practices (e.g., co-located teams), are also called collaborative construction projects (e.g., [17]).…”
Section: Introductionmentioning
confidence: 99%
“…The promising performance results of construction projects with collaborative delivery models are mainly attributed to their different elements and characteristics compared to those of traditional ones (e.g., [13,17]). These elements, which are mostly behavioral (e.g., mutual trust, open communication), have been frequently mentioned in the literature (e.g., [46][47][48]).…”
Section: Introductionmentioning
confidence: 99%